Ayahuasca no tratamento da farmacodependência ao etanol em camundongos: possível intervenção terapêutica? - Almeida, Carolina Aparecida De Faria (2019)
The treatment of ethanol addiction, a public health concern worldwide, usually is not effective and new substances have been evaluated. Accordingly, the aim of this study was to evaluate the effects of ayahuasca in ethanol-sensitized mice (Ethics Com. 34/2017). Adult male Swiss mice received 2.2 g/kg ethanol or saline i.p. on every other day for 9 days (D1, D3, D5, D7 and D9) and locomotor activity was evaluated. Then, animals were treated with ayahuasca (AYA - equivalent to 1,76 mg/kg of DMT) or water by oral gavage daily for 8 days. In the seventh day, mice were evaluated in the elevated plus maze test. After the treatment, the mice were challenged with a single dose of ethanol to measure the locomotor activity (groups: SAL/SAL/SAL, n=10; SAL/SAL/ET, n=9; SAL/AYA/ET, n=12; ET/SAL/ET, n=18; ET/AYA/ET, n=24). Immediately after that, animals were euthanized and striatum and hippocampus were dissected and stored at -80°C for Western blot analysis of D1, D2, 5HT1a and 5HT2a receptors, dynorphin, pro-dynorphin and c-Fos protein. Our results suggest that 10 alternate days of ethanol administration is able to promote the acquisition and expression of sensitization to ethanol, and eight-days treatment of ayahuasca at the dose of 1.76 mg DMT / kg of animal is effective to block the expression of sensitization to ethanol. We also observed an anxiolytic effect induced by ayahuasca. In addition, ayahuasca is able to prevent the effects of ethanol exposure on the concentration of dynorphin and c-Fos in the striatum and hippocampus, as well as the concentration of 5-HT1a and 5-HT2a receptors in the hippocampus.